2004
DOI: 10.1158/0008-5472.can-04-0172
|View full text |Cite
|
Sign up to set email alerts
|

Frequent Silencing of Low Density Lipoprotein Receptor-Related Protein 1B (LRP1B ) Expression by Genetic and Epigenetic Mechanisms in Esophageal Squamous Cell Carcinoma

Abstract: Low-density lipoprotein receptor-related protein 1B (LRP1B) is frequently deleted in tumors of various types, but its status and expression in esophageal squamous cell carcinomas (ESCs) have never been reported. In the course of a program to screen ESC cell lines for copy-number aberrations using array-based comparative genomic hybridization, we identified a homozygous deletion of LRP1B. Genomic PCR experiments revealed homozygous deletions of LRP1B in additional ESC cell lines (total, 6 of 43; 14.0%) and in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
168
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 133 publications
(178 citation statements)
references
References 23 publications
9
168
1
Order By: Relevance
“…To determine whether hypermethylation of CpG sites is associated with transcriptional silencing of the PRTFDC1 gene, we tested the promoter activity of this CpG island in OSCC cells (NA and HSC-2) using a 891-bp fragment (Fragment 1) covering the entire CpG island and 482-bp (Fragment 2) and 409-bp (Fragment 3) fragments covering uncommonly and commonly methylated regions, respectively, in cell lines without expression of PRTFDC1 (Figures 3a and b). We observed a remarkable increase in transcriptional activity of the reporter plasmid containing Fragments 1 and 3 compared with the mock reporter plasmid and reporter plasmid containing Fragment 2 in the plasmidcontaining cell lines (Figure 3b), suggesting that the CpG island around exon 1 of PRTFDC1, especially the region commonly methylated in PRTFDC1-nonexpressing cell lines, contains promoter activity, although few studies, including ours, have shown that promoter activity can be observed in fragments, especially CpG islands, not containing a 5 0 sequence around transcriptional start sites (Kolb 2003;Nakagawachi et al, 2003;Sonoda et al, 2004;Misawa et al, 2005).…”
Section: Identification Of Gene(s) Involved In the Homozygous Deletiomentioning
confidence: 83%
See 3 more Smart Citations
“…To determine whether hypermethylation of CpG sites is associated with transcriptional silencing of the PRTFDC1 gene, we tested the promoter activity of this CpG island in OSCC cells (NA and HSC-2) using a 891-bp fragment (Fragment 1) covering the entire CpG island and 482-bp (Fragment 2) and 409-bp (Fragment 3) fragments covering uncommonly and commonly methylated regions, respectively, in cell lines without expression of PRTFDC1 (Figures 3a and b). We observed a remarkable increase in transcriptional activity of the reporter plasmid containing Fragments 1 and 3 compared with the mock reporter plasmid and reporter plasmid containing Fragment 2 in the plasmidcontaining cell lines (Figure 3b), suggesting that the CpG island around exon 1 of PRTFDC1, especially the region commonly methylated in PRTFDC1-nonexpressing cell lines, contains promoter activity, although few studies, including ours, have shown that promoter activity can be observed in fragments, especially CpG islands, not containing a 5 0 sequence around transcriptional start sites (Kolb 2003;Nakagawachi et al, 2003;Sonoda et al, 2004;Misawa et al, 2005).…”
Section: Identification Of Gene(s) Involved In the Homozygous Deletiomentioning
confidence: 83%
“…We performed colony-formation assays (Sonoda et al, 2004) using the full coding sequence of PRTFDC1 with a Myc-tag cloned into a mammalian expression vector (pCMV-3Tag4A-PRTFDC1) and cells lacking expression of PRTFDC1. As shown in Figure 5, 3 weeks after transfection and subsequent selection of drug-resistant colonies, the numbers of large colonies produced by PRTFDC1-transfected NA and OM-2 cells decreased compared to those produced by empty vector-transfected cells.…”
Section: Suppressive Effect Of Prtfdc1 Expression On Cell Growth Of Omentioning
confidence: 99%
See 2 more Smart Citations
“…Array-CGH analysis was performed with the MCG Cancer Array-800, which consists of B800 BACs harbouring 800 known cancerrelated genes, and is intended for diagnosis of cancer-specific copy number aberrations (Sonoda et al, 2004). Array-CGH experiments were carried out as described previously (Takada et al, 2005) with minor modifications.…”
Section: Array-cgh Analysismentioning
confidence: 99%